Trends and mechanisms of corruption in South Korea. Issue 4 (7th August 2016) - Kalinowski, Thomas
ABSTRACT: Corruption remains one of the key obstacles to democratization and good governance. Given the nature of the subject, corruption is notoriously difficult to study. International comparisons and rankings of good governance such as the World Bank World Governance Indicators, the Bertelsmann Sustainable Governance Index, or Transparency International's Global Corruption Index are very useful for providing the big picture on corruption. To understand trends and mechanisms of corruption, however, it is necessary to conduct case studies on both successful and failed cases of anti-corruption policies. This paper investigates the successes and challenges of the fight against corruption in South Korea since the beginning of democratization in 1987. The investigation shows that Korea has generally been successful in controlling corruption. The paper argues that the remaining problems can be largely explained by the legacy of authoritarian rule and the undermining of state autonomy through the concentration of economic power.